DEVELOPMENT OF TEACHER COMPETENCIES IN DRIVING SCHOOLS - Chandra S. Haratua; Muaidin Muaidin; Abdul Goni; Holilah Rahmawati; Cahyono Kuntorojati (Sean Institute, 2023)
The Covid-19 pandemic prompted the government to reform the